2019
DOI: 10.1002/1873-3468.13369
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal mutation in helix 32 of 18S rRNA alters fidelity of eukaryotic translation start site selection

Abstract: The 40S ribosome plays a critical role in start codon selection. To gain insights into the role of its 18S rRNA in start codon selection, a suppressor screen was performed that suppressed the preferential UUG start codon recognition (Suppressor of initiation codon: Sui− phenotype) associated with the eIF5G31R mutant. The C1209U mutation in helix h32 of 18S rRNA was found to suppress the Sui− and Gcn− (failure to derepress GCN4 expression) phenotype of the eIF5G31R mutant. The C1209U mutation suppressed Sui− an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The eIF2 S264Y mutation was extensively used to study the eIF2 function [3,5,17,[23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…The eIF2 S264Y mutation was extensively used to study the eIF2 function [3,5,17,[23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Translation from these out-of-frame upORFs may preclude the translation of main ORF, resulting in the altered proteome in Sui − mutant cells. The eIF5 G31R mutation is one of the strongest Sui − mutants that preferentially recognize UUG as a start codon, unlike other Sui − mutants that can also utilize CUG or GUG as a start codon 16 , 18 . The eIF5 G31R mutation in the recessive condition is lethal, whereas the dominant eIF5 G31R mutation represses GCN4 translation (Gcn − phenotype) and shows 3-amino-1,2,4-triazole (3AT) sensitivity due to utilization of upUUG codons from the 5′ regulatory region of GCN4 transcript and show severe slow growth phenotype 19 , 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that the eIF5 G31R mutation recognizes UUG codon but does not initiate translation from CUG or GUG codon 18 . In this study, we decipher the underpinning effect of the eIF5 G31R mutation on UUG codon recognition that alters cellular proteome in dominant conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation